Ultrasound-guided axillary vein versus internal jugular vein access for totally implantable venous access ports in breast cancer: a retrospective comparison of patient-reported outcomes - He, Jianfeng; Zhang, Rong; Cai, Tianhong; Chen, Kai; Zhan, Tenghui (Frontiers in Oncology, 2025)
BackgroundPatient-centered venous access is critical in breast cancer supportive care. While the tunnel-less axillary vein (AxV) approach for totally implantable venous access port (TIVAP) implantation may improve patient experience, comparative evidence on patient-reported outcomes (PROs) against the standard internal jugular vein (IJV) approach remains limited.MethodsThis single-center retrospective cohort study compared ultrasound-guided IJV (n = 106) versus AxV (n = 102) TIVAP implantation in breast cancer patients (September 2020–February 2025). Primary outcomes included postoperative comfort (assessed at 1 day) and cosmetic outcome and satisfaction (assessed at 6 months). Complications were monitored for 6 months. Group comparisons utilized chi-square/Fisher’s exact tests. To control for potential confounders, multivariable logistic regression analyses were performed, adjusting for age, body mass index, and implantation side. Complications were monitored for 6 months.ResultsThe AxV approach significantly enhanced early postoperative comfort, with a higher rate of no discomfort (Grade 0: 72.5% vs. 59.4%, p = 0.032). At 6 months, the AxV approach demonstrated superior, favorable cosmetic outcomes (Grades 1–2: 93.1% vs. 67.9%, p < 0.001) and higher overall satisfaction (94.1% vs. 85.8%, p = 0.039). Multivariable analysis confirmed the AxV approach as an independent predictor for ideal comfort [adjusted odds ratio (aOR) = 4.48, p = 0.0002], favorable cosmetic outcome (aOR = 6.22, p < 0.001), and overall satisfaction (aOR = 3.07, p = 0.033). More AxV patients would choose the port again (83.3% vs. 72.6%, p = 0.045). The overall complication rates were comparable between groups [4.8%, 0.269/1,000 central line-days (CD) vs. 4.9%, 0.279/1,000 CD; p = 0.957].ConclusionFor breast cancer patients, the ultrasound-guided AxV approach for TIVAP provides superior early postoperative comfort, long-term cosmetic results, and patient satisfaction without increasing early complication risks, representing a significant patient-centered advancement in venous access.